Pretransplant CD4 helper function and interleukin 10 response predict risk of acute kidney graft rejection - Weimer, Rolf; Zipperle, Silvia; Daniel, Volker; Carl, Stefan; Staehler, Gerd; Opelz, Gerhard (Transplantation, 1996)
In a prospective study of 80 patients, we investigated the association of acute kidney graft rejection with pretransplant T helper/suppressor activity, B-cell responses, and in vitro cytokine secretion. Patients' CD4+ or CD8+ T cells were cocultured with control B cells and pokeweed mitogen for 6 days. SAC I was used for T cell- and monocyte-independent B-cell stimulation and pokeweed mitogen was used for T cell-dependent B-cell stimulation. B-cell differentiation was assessed in a reverse hemolytic plaque assay. Cytokine responses of T cells (interleukin[IL]-2, IL-10, γ-interferon) and B cells/monocytes (IL-6, IL-8, tumor necrosis factor-α, granulocyte-macrophage colony-stimulating factor) were determined in culture supernatants using ELISA. Subsets of CD4+ T cells, CD8+ T cells, and B cells were assessed by flow cytometry None of 12 patients with pretransplant CD4 helper defects (CD4 helper activity<10%) had acute rejection episodes, in contrast to 32 of 68 (47%) patients with normal pretransplant CD4 helper function (P=0.001). Patients with pretransplant CD4 helper defects also had better 1-year graft function than patients without CD4 helper defects (serum creatinine 1.2±0.1 mg/dl and 1.7±0.1 mg/dl, respectively,P<0.05). Pretransplant IL-10 responses were significantly associated with the occurrence of acute rejection episodes(P=0.001) and impaired 1-year graft function(P<0.001). All 14 patients with low pretransplant IL-10 responses (<100 pg/ml) had 1-year serum creatinine values of <1.5 mg/dl. Pretransplant B-cell defects and B cell/monocyte-derived cytokine secretion were not related to the incidence of graft rejection or infectious complications. Pretransplant CD8 suppressor-effector (CD11b+) cell counts were significantly associated with the occurrence of infections(P<0.05). These results show that pretransplant CD4 helper defects and low IL-10 responses predict a low risk of graft rejection, whereas Th1 (IL-2, γ-interferon) and B-cell/monocyte responses are not of predictive value.
Gesehen am 22.08.2024